Fenomena Resistensi Masyarakat Gerlang Batang terhadap Politik Uang pada Pelaksanaan Pilkades dalam Tinjauan Living Qur’an dan Dakwah - Ahmad Musyafak (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2024)
The post-reform democracy has indeed provided autonomy to villages through village head elections (pilkades). However, similar to the national level, democracy through direct elections in villages has also brought about a concerning shift in values, namely money politics, which starkly contradicts morality and religion. Amid these concerns, there remains a small portion of society that is not swayed by money politics—even collectively rejecting it as an entire village—such as Gerlang Village in Blado, Batang. Using qualitative research with a field research approach and employing phenomenology, the author seeks to explore how the people of Gerlang resist money politics from the perspective of the Living Qur'an and da’wa. The results of this study conclude that the resistance of Gerlang's community to money politics in village elections is a stance that has been cultivated since the early days of the reform era. From the perspective of the Living Qur'an, this resistance stems from a three-stage process of interpreting verse Al-Baqarah 2:188, namely cultural reception, hermeneutic reception, and aesthetic reception. This phenomenon is also rooted in the long-standing efforts of dakwah that have taken place since earlier times, specifically the era of preachers who continued the legacy of Walisongo in the region. The inheritance of Islam in the Ahlussunnah wal Jamaah tradition, imparted to the communities in Dieng and its surroundings, has become the primary foundation for understanding religious messages, including the prohibition of money politics as a form of ruswah (bribery) explicitly mentioned in the Qur'an.